Microtaxonomy of honeybees (Apis Mellifera L.) in Egypt using wing venation pattern - Mazeed, A. M. M. (2004)
From 16 Governorates in Egypt, many samples of workers honeybee were collected in order to classify them and determine the relationship between the bees morphometrically. From these samples two represent Egyptian and local Carniolan bees, while the remaining samples represent natural hybrid bees. For this purpose, a Slide-Scan connected with a computer was used to display the forewing of worker honeybee on the monitor and then 17 wing intervenation points were chosen for establishing a coordinate system representing 17 coordinate points. Performing discriminant and cluster analysis on the resulted coordinates, it could be concluded that the local Carniolan bees have a great effect on the hybrid bees, whereas the Egyptian bees were clearly separated from both Carniolan and hybrid bees in the biometrical space. ClassifYing the hybrid bees in reference to both Carniolan and Egyptian ones, the results indicated that the percentage of the hybrid bees classified as Carniolan bees was significantly higher in northern Governorates than the Egyptian bees, and vice versa in the Governorates located in the South. The biometrical relationship between the bees in the different Governorates showed that in most cases clusters of samples in the morphometrical space were close to each other geographically.
Includes reference.
Summary in Arabic.
1
Keywords: Honeybee -- Breeding -- Egypt; Honeybee -- Calssification; Honeybee -- Morphology; Apis mellifera